Inducibility of cytochrome P450-mediated 7-methoxycoumarin-O-demethylase activity in zebrafish (Danio rerio) embryos - Lörracher, Ann-Kathrin; Braunbeck, Thomas (Aquatic toxicology, 2020)
The zebrafish (Danio rerio) embryo has increasingly been used as an alternative model in human and environmental toxicology. Since the cytochrome P450 (CYP) system is of fundamental importance for the understanding and correct interpretation of the outcome of toxicological studies, constitutive and xenobiotic-induced 7-methoxycoumarin-O-demethylase (MCOD), i.e. ‘mammalian CYP2-like’, activities were monitored in vivo in zebrafish embryos via confocal laser scanning microscopy. In order to elucidate molecular mechanisms underlying the MCOD induction, dose-dependent effects of the prototypical CYP inducers β-naphthoflavone (aryl hydrocarbon receptor (AhR) agonist), rifampicin (pregnane X receptor (PXR) agonist), carbamazepine and phenobarbital (constitutive androstane receptor (CAR) agonists) were analyzed in zebrafish embryos of varying age. Starting from 36 h of age, all embryonic stages of zebrafish could be shown to have constitutive MCOD activity, albeit with spatial variation and at distinct levels. Whereas carbamazepine, phenobarbital and rifampicin had no effect on in vivo MCOD activity in 96 h old zebrafish embryos, the model aryl hydrocarbon receptor agonist β-naphthoflavone significantly induced MCOD activity in 96 h old zebrafish embryos at 46-734 nM, however, without a clear concentration-effect relationship. Induction of MCOD activity by β-naphthoflavone gradually decreased with progression of embryonic development. By in vivo characterization of constitutive and xenobiotic-induced MCOD activity patterns in 36, 60, 84 and 108 h old zebrafish embryos, this decrease could primarily be attributed to an age-related decline in the induction of MCOD activity in the cardiovascular system. Results of this study provide novel insights into the mechanism and extent, by which specific CYP activities in early life-stages of zebrafish can be influenced by exposure to xenobiotics. The study thus lends further support to the view that zebrafish embryos- at least from an age of 36 h - have an elaborate and inducible biotransformation system.
Gesehen am 24.08.2020